Hydroxide based Benzyltrimethylammonium Degradation: Quantification of Rates and Degradation Technique Development. Issue 4 (21st January 2015) - Sturgeon, Matthew R.; Macomber, Clay S.; Engtrakul, Chaiwat; Long, Hai; Pivovar, Bryan S.
Abstract : Anion exchange membranes (AEMs) are of interest as hydroxide conducting polymer electrolytes in electrochemical devices like fuel cells and electrolyzers. AEMs require hydroxide stable covalently tetherable cations to ensure required conductivity. Benzyltrimethylammonium (BTMA) has been the covalently tetherable cation that has been most often employed in anion exchange membranes because it is reasonably basic, compact (limited number of atoms per charge), and easily/cheaply synthesized. Several reports exist that have investigated hydroxide stability of BTMA under specific conditions, but consistency within these reports and comparisons between them have not yet been made. While the hydroxide stability of BTMA has been believed to be a limitation for AEMs, this stability has not been thoroughly reported. We have found that several methods reported have inherent flaws in their findings due to the difficulty of performing degradation experiments at high temperature and high pH. In order to address these shortcomings, we have developed a reliable, standardized method of determining cation degradation under conditions similar/relevant to those expected in electrochemical devices. The experimental method has been employed to determine BTMA stabilities at varying cation concentrations and elevated temperatures, and has resulted in improved experimental accuracy and reproducibility. Most notably, these results have shown that BTMA is quite stable at 80°C (half-life of ∼4 years), a significant increase in stability over what had been reported previously.